Risk preferences in surrogate decision making - Batteux, Eleonore (2020)
Decision research has long focused on how we make decisions for ourselves, yet a considerable proportion of the personal and professional decisions we make are on behalf of others, which we term surrogate decisions. This thesis investigates the psychological processes involved in surrogate decision making. It features a first set of studies which compare financial and medical surrogate decisions and a second which address the complex process of making difficult medical decisions for our loved ones. This thesis makes valuable contributions to the field by providing empirical, theoretical, methodological and practical insights into making decisions on behalf of other people.